33-10x=-12x

Simple and best practice solution for 33-10x=-12x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 33-10x=-12x equation:



33-10x=-12x
We move all terms to the left:
33-10x-(-12x)=0
We get rid of parentheses
-10x+12x+33=0
We add all the numbers together, and all the variables
2x+33=0
We move all terms containing x to the left, all other terms to the right
2x=-33
x=-33/2
x=-16+1/2

See similar equations:

| 1/2x+3/2-3/2x=1/6 | | 3/4x+1=10 | | 12=5/6x | | 15x-12=11x+12 | | 10-(-4c)=34 | | 8x-12=6x-34 | | 4x=24+6x | | (5/4)x-(1/8)x=(9/8)x | | 4x^2-4x+28=X-4 | | 3+2m=-28 | | m+5(m-+1)=7 | | 12t+-4=3+5t | | 12+p(5/7-2/7)=6 | | (5/4)x-(1/8)x=(9/8)+x | | 2(12x+8)+3x=-146 | | v(v-4)(v+7)=0 | | v=30+v | | 7(a+8)=91 | | -3(x+4)-2=2(x-1)+4 | | -6x+17=41 | | 4.05p+14.5=4.5(p+3) | | q+|6.4|=9.6 | | −9(t−2)=4(t−15) | | 4(t-5)=20 | | 2(-7x-6)=-110 | | 11y+6=15y-14 | | 3/k-1/10k=1/2k+1 | | −3=h+8÷2 | | 16.87=x+(2*2.5/x) | | 86=264-u | | 7+4(3n+7)=-25-3n | | −9(t−2)=4(t−15)−9(t−2)=4(t−15) |

Equations solver categories